Uterine junctional zone thickness in infertile women evaluated by MRI. Issue 3 (18th August 2016) - Meylaerts, Liesbeth J.; Wijnen, Leen; Ombelet, Willem; Bazot, Marc; Vandersteen, Marjan
Abstract : Purpose: To prospectively evaluate and compare the junctional zone (JZ) and outer myometrial thickness in infertile and healthy nulliparous women at different locations in the uterine wall during the menstrual cycle by magnetic resonance imaging (MRI). Materials and Methods: We performed pelvic 1.5T MRI ( T 2 ‐weighted turbo spin echo sequences) on 28 infertile women: 5 with infertility of unknown origin, 12 anovulating, and 11 on ovarian stimulation therapy (mean age 28.5, 30.8, and 29.3 years, respectively); and a control group consisting of 18 healthy nulliparous volunteers (mean age 26.4 years). The women with unknown infertility origin and the control group underwent MRI investigations during their follicular, ovulatory, and luteal phase. The JZ and outer myometrial thicknesses were measured at six locations in the uterine wall: anterior and posterior wall of the isthmus, midcorpus, and fundus. Results: The JZ in the anovulating women at the posterior wall of the isthmus (4.2 mm) was significantly thicker compared to the control group (3.2, 3.0, and 2.9 mm, in respectively the three menstrual phases) ( P  = 0.027). The outer myometrium in the anovulating women was significantly thicker at all measured locations (average 11.5 mm) in comparison to the control group (8.1, 8.0, and 8.5 mm, in respectively the three menstrual phases) ( P < 0.050). The infertile women on ovarian stimulation therapy showed a significantly thicker outer myometrium at the anterior wall (isthmus, midcorpus, and fundus) ( P < 0.050). Conclusion: The results indicate that a thickened JZ, and especially a thickened outer myometrium, might be associated with infertility. Level of Evidence: 1 J. Magn. Reson. Imaging 2017;45:926–936.